2016
DOI: 10.1212/wnl.0000000000003157
|View full text |Cite
|
Sign up to set email alerts
|

Cognition in school-age children exposed to levetiracetam, topiramate, or sodium valproate

Abstract: Preconception counseling should include discussion of neurodevelopmental outcomes for specific treatments and their doses and women should be made aware of the limited nature of the evidence base for newer antiepileptic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
117
4
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(133 citation statements)
references
References 27 publications
8
117
4
4
Order By: Relevance
“…In the mothers not taking folic acid supplementation, 63% (n = 5) of AED-exposed children had language Table 1 Characteristics of children of mothers with and without epilepsy Characteristics AED-exposed children of mothers with epilepsy n = 346 AED-unexposed children of mothers with epilepsy n = 388 15 (5) 17 (4) 2418 (2) Maternal report of seldom/never helping their child read letters and sounds during a typical week at age 5 years 17 (15) 22 (15) 6675 (16) Maternal report of never reading to their child at age 8 years 6 (5) 9 (6) 2959 (7) Language impairment age 1.5 years i 43 (20) 24 (9) 7896 (11) Language impairment age 3 years j 22 (12) 14 (7) 4182 (7) AED, antiepileptic drug; BMI, body mass index; TC seizure(s), tonic-clonic seizure(s). N may vary within the groups due to missing data.…”
Section: Maternal Folate Status and Language Impairmentmentioning
confidence: 99%
“…In the mothers not taking folic acid supplementation, 63% (n = 5) of AED-exposed children had language Table 1 Characteristics of children of mothers with and without epilepsy Characteristics AED-exposed children of mothers with epilepsy n = 346 AED-unexposed children of mothers with epilepsy n = 388 15 (5) 17 (4) 2418 (2) Maternal report of seldom/never helping their child read letters and sounds during a typical week at age 5 years 17 (15) 22 (15) 6675 (16) Maternal report of never reading to their child at age 8 years 6 (5) 9 (6) 2959 (7) Language impairment age 1.5 years i 43 (20) 24 (9) 7896 (11) Language impairment age 3 years j 22 (12) 14 (7) 4182 (7) AED, antiepileptic drug; BMI, body mass index; TC seizure(s), tonic-clonic seizure(s). N may vary within the groups due to missing data.…”
Section: Maternal Folate Status and Language Impairmentmentioning
confidence: 99%
“…5 Behavioral problems occur predominantly in valproate (VPA)-exposed children 3,6-11 ; they have a higher risk of autism spectrum disorders (ASDs) [12][13][14] and attention-deficit/hyperactivity disorder (ADHD). 11 Because most studies, so far, used different methodologies, in children of different ages, using different rating systems, this may have led to different results. 3,6,7,9 The only study that examined behavioral functioning of school-aged children exposed to levetiracetam (LEV) found no risk of behavioral problems.…”
Section: Introductionmentioning
confidence: 99%
“…They found no difference between the developmental scores of levetiracetam prenatally exposed children and controls, while VPA-exposed children scored, on average, 15.8 points below that of children exposed to levetiracetam on measures of gross motor skills (95% CI, 24.5-27.1; p < 0.001), 6.4 points below on comprehension language abilities (95% CI, 11.0-21.8; p 5 0.005), and 9.5 points below on expressive language abilities (95% CI, 14.7-24.4; p < 0.001) (Shallcross et al, 2014). Bromley et al (2016) also found that 42 children born to levetiracetam treated mothers had similar developmental scores to 55 control children . In summary, levetiracetam seems to be a relatively safe drug in pregnancy.…”
Section: Levetiracetammentioning
confidence: 99%
“…Over half of the exposed children received speech, occupational, or physical therapy (Rihtman et al, ). In a recently published study, Bromley et al () compared the cognitive functioning of children exposed to levetiracetam ( n = 42), topiramate ( n = 27), or valproate ( n = 47), and control children ( n = 55). They reported no association between the IQ, memory, language, or attentional abilities, and prenatal exposure to levetiracetam or topiramate, although the children born to VPA‐treated mothers had developmental delays (Bromley et al, ).…”
Section: Mood Stabilizersmentioning
confidence: 99%